Micro-nano carbon particles and preparation method thereof

By using the combination of disbigneys and grinding liquids in the preparation of micro -nano -carbon particles to destroy the cross -linked bonds of carbon materials and reduce the hardness of the fine particles, solve the problem of "crushing limit", and achieve efficient micro -nanogenic preparation.

CN116409779BActive Publication Date: 2025-01-28SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111657677.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-30
Publication Date
2025-01-28
Estimated Expiration
2041-12-30

AI Technical Summary

Technical Problem

In the prior art, there is a "milling limit" in the preparation of micro-nanocarbon particles, that is, during physical crushing, the ultrafine particles have larger specific surface energy, and there is a "milling-aggregation" phenomenon, making it difficult to achieve micro-nanocarbon with smaller particle sizes. Preparation of materials.

Method used

Adopting the "hard bubble and soft mill" strategy, first use the deconstructed agent with the ability to disburs and mixes with the carbon material to destroy the cross -linking bond, improve the order of the crystal, and use the dissolution of the abrasive to reduce the new generation of new generation. The hardness of fine particles promotes its broken.

Benefits of technology

The micro -nanogenicization of carbon materials broke through the "crushing limit" and obtained more than 50 % of the micrometers with a particle size of less than or equal to 1 micron, and more than 90 % of the microman carbon particles with a particle size of less than 2 microns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116409779B_ABST
    Figure CN116409779B_ABST
Patent Text Reader

Abstract

The present invention discloses a micro-nano carbon particle and a preparation method. More than 50% of the micro-nano carbon particles have a particle size less than or equal to 1 micron, and more than 90% of the particle size is less than 2 microns. The preparation method is as follows: 1) coarsely crushing the carbon particle raw material to obtain feed particles; 2) mixing the feed particles with a deconstruction liquid, stirring, and then performing solid-liquid separation 1 to obtain deconstructed particles; 3) mixing the deconstructed particles with a grinding liquid, a reagent 1, and a reagent 2, and then grinding to obtain a grinding slurry; 4) performing solid-liquid separation 2 on the grinding slurry to obtain micro-nano carbon particles. The present invention first uses a deconstructor and a deconstruction liquid with deconstruction ability to deconstruct the carbon material, destroy the cross-linking bonds in the carbon material, so that the molecular structure is rearranged in a directional manner, the order of the crystal is improved, and at the same time, the small molecules in the carbon material structure are leached, so that the macroporous structure of the carbon material is increased, and the stress points are increased, thereby deepening the subsequent grinding degree and improving the crushing degree of the carbon particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material technology, and specifically relates to micro-nano carbon particles and a preparation method thereof. Background Art

[0002] Due to their size effect advantages, micro-nano particles have properties that do not exist in other lower scales in terms of optics, acoustics, magnetism, mechanics, thermal, and surface and interface properties. Therefore, they can be used as high-performance components in the fields of microelectronic devices, optoelectronic materials, medical imaging, ceramic preparation, biomaterials, new functional plastics, catalytic reactions, fuel combustion, dyes and paints, military manufacturing, aerospace, and environmental protection. Micro-nano carbon materials have excellent surface and interface effects such as rich surface area and developed pore structure, rich preparation raw materials, and non-toxicity, and have competitive advantages in the above fields.

[0003] The most critical factor of micro-nano carbon materials is particle size. The preparation process of micro-nano materials can be divided into physical crushing, chemical synthesis, supercritical preparation and combustion preparation. Among them, physical crushing uses the generation and expansion of cracks in particle crystal defects under stress to achieve the purpose of micro-nano crushing. However, the problem with physical crushing is that in the physical crushing process, the ultrafine particles have a large specific surface energy and there is a "crushing-agglomeration" phenomenon, which makes the physical crushing have a "crushing limit", that is, after reaching the "limit particle size", as the grinding time increases, the particle size is unlikely to decrease, which reduces the crushing energy utilization efficiency, and it is also difficult to truly realize the preparation of micro-nano carbon materials with smaller particle sizes.

[0004] Therefore, how to break through the "crushing limit" is a key issue in the preparation of micro-nano carbon particles.

[0005] In order to solve the above problems, the present invention is proposed. Summary of the invention

[0006] In view of the "crushing limit" problem in the prior art, the present invention provides a method for preparing micro-nano carbon particles, which can solve the technical problems existing in the prior art.

[0007] The present invention adopts the strategy of "hard foaming and soft grinding". First, a deconstructing agent and a deconstructing liquid with deconstructing ability are mixed with the carbon material. Due to the deconstructing effect, the cross-linking bonds in the carbon material are destroyed, so that the molecular structure is rearranged in a directional manner, thereby improving the order of the crystal. In this process, small molecules in the carbon material structure are leached, the cross-linking structure is further destroyed, and the side chain weak bond groups are removed, thereby making the material loose, and the macroporous structure is increased, and the stress points are increased, which is conducive to the micro-nanoization of carbon particles. Then, deconstructing particles are prepared. Subsequently, the deconstructing particles are mixed with a grinding liquid mixed with a pharmaceutical agent, and then micro-nano crushing is performed. At the same time, the grinding liquid also has a certain deconstructing ability. During the grinding process, its diffusion in the particles is promoted, the deconstructing ability is strengthened, the hardness of the newly generated fine particles is reduced, and stress points are formed inside them. The molecular structure with a deeper directional order is conducive to the occurrence of inter-crystal crushing. The present invention can realize the micro-nanoization of carbon materials in an environmentally friendly and efficient manner.

[0008] The first aspect of the present invention provides micro-nano carbon particles, wherein more than 50% of the micro-nano carbon particles have a particle size less than or equal to 1 micron, and more than 90% of the micro-nano carbon particles have a particle size less than 2 microns.

[0009] The second aspect of the present invention provides a method for preparing the micro-nano carbon particles according to the first aspect of the present invention, comprising the following steps:

[0010] 1) After the carbon particle raw material is coarsely crushed, it is screened to obtain feed particles with a certain particle size, and the return particles that do not meet the feed particle size are sent back to the coarse crushing step;

[0011] 2) Mixing the feed particles and the deconstruction liquid in a certain mass ratio, stirring for a certain period of time, and then performing solid-liquid separation 1 to obtain deconstruction particles and deconstruction circulating liquid;

[0012] 3) mixing the dissociated particles with the grinding liquid, the reagent 1 and the reagent 2 in a certain mass ratio and grinding them, and discharging the materials after a certain total grinding time to obtain a grinding slurry;

[0013] 4) The grinding slurry is subjected to solid-liquid separation 2 to obtain micro-nano carbon particles and grinding circulating liquid.

[0014] Preferably, the carbon particle raw material in step (1) is one or more of coal, activated carbon, petroleum coke, semi-coke, gasification residue, biochar or graphite; and the certain particle size is 20 to 300 μm.

[0015] Preferably, the deconstruction liquid described in step (2) is one or more of methanol, ethanol, toluene, acetone, butanone, chlorobenzene, o-dichlorobenzene, propionaldehyde, ether, benzene, sulfur dicarbonate, water, gasoline or diesel; the mass ratio of feed particles to deconstruction liquid is: feed particles: deconstruction liquid = 100:0-3000; the stirring time is 30 seconds to 7 days.

[0016] Preferably, a deconstructing agent can also be added in step (2), that is, the feed particles are mixed with the deconstructing agent and the deconstructing liquid in a mass ratio, and the deconstructing agent is one or more of tetralin, hydrogen tetrachloride, tetrahydrofuran, trihaloalkane, pyridine, sodium hydroxide, hydrogen peroxide, n-hexane, urea, isopropanol, N-methylpyrrolidone, pentafluorobenzonitrile, octafluorotoluene, ethyl acetate, N,N,N,N-tetramethylenediamine or ionic liquid. The mass ratio of the feed particles, the deconstructing liquid and the deconstructing agent is: feed particles: deconstructing liquid: deconstructing agent = 100:0~3000:0~100; the certain stirring time is 30 seconds to 7 days. That is to say, the deconstructing process of the present invention further includes a deconstructing agent, and the deconstructing agent can further improve the deconstructing effect. Liquid deconstructors, such as tetralin, hydrogen tetrachloride, tetrahydrofuran, trihaloalkanes, and pyridine, also have certain deconstruction capabilities when used alone, but they are relatively expensive, so they are only added in small amounts in the present invention as a component to enhance the deconstruction effect of the deconstruction liquid. Solid deconstructors, such as sodium hydroxide and urea, need to be dissolved in the deconstruction liquid to have a deconstruction effect and can promote the deconstruction effect of the deconstruction liquid.

[0017] Preferably, the deconstruction circulating liquid obtained after solid-liquid separation 1 in step (2) can be used as the deconstruction circulating liquid of the next process before solid-liquid separation 1 in step (2), that is, in step (2), the feed particles are mixed with the deconstruction liquid and the deconstruction circulating liquid in a mass ratio, wherein the mass ratio of the feed particles, the deconstruction liquid and the deconstruction circulating liquid is: feed particles: deconstruction liquid: deconstructing agent: deconstruction circulating liquid = 100: 0-3000: 0-3000. More preferably, a deconstructing agent is further added in step (2), and the feed particles are mixed with the deconstruction liquid, the deconstructing agent and the deconstruction circulating liquid in a certain mass ratio, wherein the certain mass ratio is: feed particles: deconstruction liquid: deconstructing agent: deconstruction circulating liquid = 100: 0-3000: 0-100: 0-3000.

[0018] Preferably, the grinding liquid in step (3) is one or more of tetralin, hydrogen tetrachloride, tetrahydrofuran, trihaloalkane, pyridine, methanol, ethanol, toluene, acetone, propionaldehyde, ether, benzene, sulfur dicarbonate, water, gasoline, diesel, acetonitrile, acetylacetone, dimethyl sulfoxide or butyrolactone; the agent 1 is sorbitan oleate, sorbitan trioleate, oleic acid, fatty acid ammonium salt, anionic aliphatic ester, modified polyurethane polymer, paraffin, low molecular weight One or more of waxes, naphthalene sulfonate formaldehyde condensate, sodium lignin sulfonate, polyacrylic acid, polycarboxylates, humic acids, polyolefins, rosins, polyoxyethylenes, polyethers, sodium hexametaphosphate, titanates, betaine, nonylphenol ethoxysulfates, Tween, Span or inorganic salts; the agent 2 is one or more of polyethylene glycol, lecithin, starch, hydrogenated castor oil, xanthan gum, guar gum, polyacrylamide, Triton, ionic liquid or linear alcohol ethoxylate.

[0019] Preferably, the certain mass ratio described in step (3) is: dissociating particles: grinding liquid: agent 1 = 100: 0-3000: 0-100; the mass ratio of the certain agent 2 to the total grinding liquid is 0.01-20: 100; the grinding method is a medium stirred mill, a ball mill, a planetary mill or a high-speed rotary mill.

[0020] Preferably, the grinding circulating liquid obtained after solid-liquid separation 2 in step (4) can be used as the grinding circulating liquid of the next process in step (3), that is, in step (3), the dissociated particles and the grinding liquid, the grinding circulating liquid and the first agent are mixed in a certain mass ratio and then ground, wherein the certain mass ratio is: dissociated particles: grinding liquid: grinding circulating liquid: first agent = 100: 0~3000: 0~3000: 0~100.

[0021] The third aspect of the present invention provides a method for improving the degree of carbon particle crushing. The carbon material is firstly decomposed using a deconstructing agent and a deconstructing liquid with decomposition ability, thereby destroying the cross-linking bonds in the carbon material, causing a directional rearrangement in the molecular structure, improving the order of the crystal, and at the same time leaching small molecules in the carbon material structure, thereby increasing the macroporous structure of the carbon material and increasing the stress points, thereby deepening the subsequent grinding degree and improving the degree of carbon particle crushing.

[0022] Preferably, the grinding liquid used in the grinding process of the present invention also has dissociation ability. During the grinding process, the diffusion effect in the carbon particles is promoted, the dissociation ability is strengthened, the hardness of the newly generated fine particles is reduced, stress points are formed inside them, and a deeper directional and ordered molecular structure is conducive to the occurrence of inter-crystal crushing.

[0023] In the present invention, medicine 1 is the first medicine, and medicine 2 is the second medicine. Solid-liquid separation 1 is the first solid-liquid separation, and solid-liquid separation 2 is the second solid-liquid separation.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention adopts the "deconstruction-grinding" method for the first time. First, a deconstructing agent and a deconstructing liquid with deconstruction ability are used to deconstruct the carbon material, destroy the cross-linking bonds in the carbon material, so that the molecular structure is rearranged in a directional manner, the order of the crystal is improved, and at the same time, the small molecules in the carbon material structure are leached, thereby increasing the macroporous structure of the carbon material and increasing the stress points, thereby deepening the subsequent grinding degree and improving the degree of carbon particle crushing.

[0026] 2. Furthermore, the grinding liquid used in the grinding process of the present invention also has the ability to dissociate. During the grinding process, the diffusion effect in the carbon particles is promoted, the dissociation ability is strengthened, the hardness of the newly generated fine particles is reduced, and stress points are formed inside them. The deeper directional and ordered molecular structure is conducive to the occurrence of inter-crystal fragmentation, thereby breaking through the "crushing limit" to obtain micro-nano carbon particles.

[0027] 3. The present invention can realize micro-nano carbon material in an environmentally friendly and efficient manner. The micro-nano carbon particles prepared by the preparation method of the present invention have a particle size of more than 50% less than or equal to 1 micron, and more than 90% less than 2 microns.

[0028] 4. The grinding method of the present invention adopts wet grinding, which is environmentally friendly and has a simple and easy preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The preparation process flow chart of the present invention;

[0030] Figure 2 Flow chart of materials in the preparation process of the present invention;

[0031] Figure 3 Particle size distribution diagram of carbon particles obtained in comparative examples and examples of the present invention. DETAILED DESCRIPTION

[0032] The present invention is described below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto. The experimental methods for which specific conditions are not specified in the examples are generally carried out according to conventional conditions and conditions described in the manual, or according to the general equipment, materials, reagents, etc. used according to the conditions recommended by the manufacturer, and unless otherwise specified, all can be obtained from commercial sources. The raw materials required in the following examples and comparative examples are all commercially available.

[0033] Comparative Example:

[0034] After the coal particles are coarsely crushed, they are screened to obtain feed particles of 75 to 150 μm, and the return particles that do not meet the feed particle size are sent back to the coarse crushing step. Based on the mass percentage, the feed particles are mixed with methanol, nonylphenol ethoxysulfuric acid, and linear alcohol ethoxylate at a ratio of 100:300:1:0.05 and then input into a medium stirring mill. After grinding for 3 hours, the material is discharged to obtain a grinding slurry. The grinding slurry is mechanically filtered to obtain micro-nano carbon particles and a grinding circulating liquid. The particle size distribution of the obtained carbon particles is as follows Figure 3 As shown in the comparative example.

[0035] Implementation Case 1:

[0036] After the coal particles are coarsely crushed, they are screened to obtain feed particles of 75 to 150 μm, and the return particles that do not meet the feed particle size are sent back to the coarse crushing step. Based on the mass percentage, the feed particles are mixed with ethanol at a ratio of 100:400, stirred for 20 hours, and then mechanically filtered to obtain deconstructed particles and deconstructed circulating liquid. Based on the mass percentage, the deconstructed particles are mixed with methanol, nonylphenol ethoxysulfate, and linear alcohol ethoxylate at a ratio of 100:300:1:0.05 and input into a medium stirred mill. After grinding for 3 hours, the material is unloaded to obtain a grinding slurry. The grinding slurry is mechanically filtered to obtain micro-nano carbon particles and a grinding circulating liquid. The particle size distribution of the obtained micro-nano carbon particles is as follows Figure 3 As shown in Case 1.

[0037] Implementation Case 2:

[0038] After the coal particles are coarsely crushed, they are screened to obtain feed particles of 100-150 μm, and the return particles that do not meet the feed particle size are sent back to the coarse crushing step. Based on the mass percentage, the feed particles are mixed with methanol at a ratio of 100:400, stirred for 5 minutes, and then mechanically filtered to obtain deconstructed particles and deconstructed circulating liquid. Based on the mass percentage, the deconstructed particles are mixed with water, polyether, and xanthan gum at a ratio of 100:900:5:0.05, input into a medium stirring mill, and discharged after a total grinding of 3 hours to obtain a grinding slurry. The grinding slurry is mechanically filtered to obtain micro-nano carbon particles and a grinding circulating liquid. The particle size distribution of the obtained micro-nano carbon particles is as follows Figure 3 As shown in Case 2.

[0039] Implementation Case 3:

[0040] Compared with the implementation case 1, in this case, the slurry was directly added with chemicals and then ground after slurrying instead of filtering after dissolution.

[0041] After the coal particles are coarsely crushed, they are screened to obtain feed particles of 150 to 300 μm, and the return particles that do not meet the feed particle size are sent back to the coarse crushing step. Based on the mass percentage, the feed particles are mixed with methanol at a ratio of 150:400 and stirred for 24 hours. Based on the mass percentage, the mixed material, sodium hexametaphosphate, and Triton are mixed at a ratio of 550:5:0.1 and input into a medium stirring mill. After grinding for 5 hours, the material is unloaded to obtain a grinding slurry. The grinding slurry is mechanically filtered to obtain micro-nano carbon particles and a grinding circulating liquid. The particle size distribution of the obtained micro-nano carbon particles is as follows Figure 3 As shown in Case 3.

[0042] Implementation Case 4:

[0043] Compared with Implementation Case 2, a deconstructing agent, N-methylpyrrolidone, is added in this case.

[0044] After the coal particles are coarsely crushed, they are screened to obtain feed particles of 100-150 um, and the return particles that do not meet the feed particle size are sent back to the coarse crushing step. The feed particles are mixed with methanol and N-methylpyrrolidone at a ratio of 100:400:10, stirred for 5 minutes, and then mechanically filtered to obtain deconstructed particles and deconstructed circulating liquid. The deconstructed particles are mixed with water, polyether, and xanthan gum at a ratio of 100:900:5:0.05 and input into a medium stirring mill. After a total grinding of 3 hours, the material is discharged to obtain a grinding slurry. The grinding slurry is mechanically filtered to obtain micro-nano carbon particles and a grinding circulating liquid. The particle size distribution of the obtained micro-nano carbon particles is as follows Figure 3 As shown in Case 4.

[0045] pass Figure 3 It can be seen that the particle size of the carbon particles obtained in the comparative example is mostly concentrated at about 6μm, while the particle size of the micro-nano carbon particles obtained in Case 1 of the present invention is mostly concentrated at about 1μm, which is much smaller than the comparative example. Furthermore, the particle size of the micro-nano carbon particles obtained in Case 2 is partially concentrated at about 0.07μm, and the particle size of the micro-nano carbon particles obtained in Case 3 is partially concentrated at about 0.2μm. In Case 4, the proportion of small particle size increases on the basis of Case 2, which shows that the method of the present invention breaks the "crushing limit", and continued grinding can further crush the particles to achieve micro-nanoization, and adding a small amount of deconstructor can further increase the proportion of small particle size.

[0046] The above embodiments describe the basic principles and main features of the present invention and the advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention, and are not intended to limit the scope of the present invention in any way. Without departing from the scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the protection claimed.

Claims

1. A method for preparing micro-nano carbon particles, wherein more than 50% of the micro-nano carbon particles have a particle size less than or equal to 1 micron, and more than 90% of the micro-nano carbon particles have a particle size less than 2 microns, characterized in that: The preparation method comprises the following steps: (1) Coal particles are coarsely crushed and then sieved to obtain feed particles of 100-150 μm; (2) Mixing and stirring the feed particles, the deconstruction agent and the deconstruction liquid in a mass ratio, performing a first solid-liquid separation, and obtaining deconstruction particles and a deconstruction circulating liquid, wherein the deconstruction liquid is methanol, the deconstruction agent is N-methylpyrrolidone, and the mass ratio of the feed particles, the deconstruction liquid and the deconstruction agent is: feed particles: deconstruction liquid: deconstruction agent = 100:400:10, and the stirring time is 5 min; (3) mixing the dissociative particles with a grinding liquid, a first agent, and a second agent in a mass ratio and grinding them, and discharging the materials after the total grinding time to obtain a grinding slurry, wherein the grinding liquid is water, the first agent is polyether, and the second agent is xanthan gum. The mass ratio of the dissociative particles, the grinding liquid, the first agent, and the second agent is: dissociative particles: grinding liquid: first agent: second agent = 100:900:5:0.

05. The grinding method is a medium stirred mill, and the total grinding time is 3 hours. (4) The grinding slurry is subjected to a second solid-liquid separation to obtain micro-nano carbon particles and a grinding circulating liquid.

2. The preparation method according to claim 1, characterized in that: The deconstruction circulating liquid obtained after the first solid-liquid separation in step (2) is used as the deconstruction circulating liquid of the next process before the first solid-liquid separation in step (2).

3. The preparation method according to claim 1, characterized in that: The grinding circulating liquid obtained after the second solid-liquid separation in step (4) is used as the grinding circulating liquid for the next process in step (3).

Citation Information

Patent Citations

  • Graphene coated lithium titanate cathode and preparation method thereof

    CN104638267A

  • Method for preparing carbon nano particles and carbon dots by using activated carbon as precursor

    CN108910862A

  • Coal mine milling system with coarse particle recycling function

    CN204194087U